The impact of intermittent exercise in a hypoxic environment on redox status and cardiac troponin release in the serum of well-trained marathon runners - Li, F.; Nie, J.; Lu, Y.; Tong, T. K. K.; Yi, L.; Yan, H.; Fu, F. H. K.; Ma, S. (European Journal of Applied Physiology, 2016)
Purpose: To investigate the effects of hypoxic training on redox status and cardiac troponin (cTn) release after intermittent exercise. Method: Nine well-trained male marathon runners (age, 21.7 ± 2.3 year; body mass, 64.7 ± 4.8 kg; height, 177.9 ± 3.8 cm; and VO2max, 64.3 ± 6.7 ml/kg/min) completed intermittent exercise under normoxic [trial N; fraction of inspiration oxygen (FIO2), 21.0 %] and hypoxic (trial H; FIO2, 14.4 %) conditions in random order. Each bout of intermittent exercise included hard run (16.2 ± 0.8 km/h) at 90 % VO2max for 2 min followed by easy run (9.0 ± 0.4 km/h) at 50 % VO2max for 2 min and 23 bouts in 92 min totally. Malondialdehyde, reduced glutathione (GSH), superoxide dismutase, an estimate of total antioxidant capacity (T-AOC), high-sensitivity cardiac troponin T (hs-cTnT), and cardiac troponin I (cTnI) were measured before, immediately after (0 h), and 2, 4, and 24 h after the completion of trials N and H. Result: GSH was increased immediately after trial N. T-AOC was lower 4 h after trial H than trial N. Hs-cTnT was elevated from 0 to 4 h and returned to baseline 24 h after both trials. CTnI was increased after trial H; peaked at 2-4 h and returned to below the detection by 24 h. Conclusion: The overall redox status was balanced under normoxic conditions, and exercise-induced cTn release did not deviate. However, the protective effects of antioxidant were weaker in the hypoxic state than normoxic, and the stress on the myocardium induced by intermittent exercise was transiently aggravated.